Intercellular adhesion molecule-1 polymorphisms, K469E and G261R and susceptibility to vasculitis and rheumatoid arthritis: a meta-analysis - Lee, Y. H.; Bae, S-C. (Cellular and Molecular Biology, 2016)
The aim of this study was to determine whether intercellular adhesion molecule-1 (ICAM-1) polymorphisms are associated with susceptibility to vasculitis or rheumatoid arthritis (RA). Meta-analyses were performed to assess the associations between K469E and G241R polymorphisms of ICAM-1 and vasculitis or RA. A total of 12 studies on 1,368 patients and 1,922 controls, which comprised 8 vasculitis studies and 4 RA studies, were included in the meta-analysis. We found no significant association between vasculitis and K469E E allele among the various subjects (OR = 1.238, 95% CI = 0.9781–1.566, p = 0.076). However, an association between vasculitis and K469E polymorphism was observed under homozygote contrast (OR = 1.443, 95% CI = 1.084–1.920, p = 0.012). Stratification by ethnicity and vasculitis type showed no association between vasculitis and 1 K469E polymorphism under heterozygote contrast. In addition, the meta-analysis revealed a significant association between the ICAM-1 G241R R allele and Behcet's disease (BD) (OR = 3.261, 95% CI = 1.653–6.434, p = 0.001), but not giant cell arteritis. Moreover, the meta-analysis indicated an association between RA and the R allele and RR+ RG genotype of the ICAM-1 G241R polymorphism (OR = 2.014, 95% CI = 1.215–3.339, p = 0.007; OR = 2.394, 95% CI = 1.354–4.235, p = 0.003). This meta-analysis suggests that the K469E polymorphism is associated with susceptibility to vasculitis, and that the G241R polymorphism is associated with susceptibility to BD and RA.